A QUALITATIVE STUDY: THE MANAGEMENT OF DIARRHEA AMONG TODDLERS - Barni Barni; Dewie Sulistyorini (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Diarrhea is a prime cause of morbidity in infants. Early in 2018, There were 141 cases in Beji Village, Banjarmangu Sub-district. The government had an effort to prevent diarrhea, one of which is by conducting socialization to the community. Mothers' knowledge of diarrhea disease needs has a significant influence in suppressing diarrhea. This study aimed to identify community points of view about the classification, prevention, and treatment of diarrhea. This study used a qualitative study method. Data Collected by Depth interview with 13 people in Beji Village, Banjarmangu Sub-district, Banjarnegara District. The results showed that the community had a different classification between diarrhea and 'luganen'. Diarrhea considered a disease, and luganen is a sign of growth and development. Diarrhea prevents by maintaining a clean and healthy lifestyle. Diarrhea treats using a mixture of guava leaves and turmeric as first aid. The infant will be brought to health facilities when the symptoms appear and become severer.Keywords: Local knowledge, prevention, treatment, diarrhea